Directly reprogrammed Huntington's disease neural precursor cells generate striatal neurons exhibiting aggregates and impaired neuronal maturation. (27th May 2021) - Monk, Ruth; Lee, Kevin; Jones, Kathryn S.; Connor, Bronwen
Abstract: Huntington's disease (HD) is an autosomal dominant neurodegenerative disorder characterized by the progressive loss of striatal medium spiny neurons. Using a highly efficient protocol for direct reprogramming of adult human fibroblasts with chemically modified mRNA, we report the first generation of HD induced neural precursor cells (iNPs) expressing striatal lineage markers that differentiated into DARPP32+ neurons from individuals with adult‐onset HD (41‐57 CAG). While no transcriptional differences between normal and HD reprogrammed neurons were detected by NanoString nCounter analysis, a subpopulation of HD reprogrammed neurons contained ubiquitinated polyglutamine aggregates. Importantly, reprogrammed HD neurons exhibited impaired neuronal maturation, displaying altered neurite morphology and more depolarized resting membrane potentials. Reduced BDNF protein expression in reprogrammed HD neurons correlated with increased CAG repeat lengths and earlier symptom onset. This model represents a platform for investigating impaired neuronal maturation and screening for neuronal maturation modifiers to treat HD. Abstract : Directly reprogrammed Huntington's disease induced neural precursor cells generate DARPP32+ striatal neurons exhibiting ubiquitinated huntingtin aggregates, altered neuronal morphologies, reduced hyperpolarization, and reduced BDNF expression that correlates with age of symptom onset and increased CAG expansion.